2006
DOI: 10.1159/000096300
|View full text |Cite
|
Sign up to set email alerts
|

Reported Alcohol Consumption and Cognitive Decline: The Northern Manhattan Study

Abstract: Background: Moderate alcohol intake may slow cognitive decline, and both vascular and neurodegenerative mechanisms have been implicated. Methods: We examined reported alcohol intake and cognitive decline in a community-based cohort of Hispanic, black and white individuals (n = 1,428). The role of the apolipoprotein E Ε4 (APOE4) allele as a modifier was also studied. Results and Conclusions: Reported drinking was as follows: 300 participants (21%) were ‘never’ drinkers, 622 (44%) ‘past’ drinkers, 145 (10%) repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 66 publications
1
23
0
2
Order By: Relevance
“…Data were collected through interviews by trained bilingual research assistants using standardized data collection instruments [17,24,25] . Educational level was used as an indicator of socioeconomic status (SES) and classified into 2 categories: 'Less than eighth-grade education' included those who never went to high school and 'more than eighth-grade education' was used as the reference.…”
Section: Risk Factors and Covariatesmentioning
confidence: 99%
“…Data were collected through interviews by trained bilingual research assistants using standardized data collection instruments [17,24,25] . Educational level was used as an indicator of socioeconomic status (SES) and classified into 2 categories: 'Less than eighth-grade education' included those who never went to high school and 'more than eighth-grade education' was used as the reference.…”
Section: Risk Factors and Covariatesmentioning
confidence: 99%
“…A number of recent articles have shown that older adults who drink alcohol at light to moderate levels have better cognitive performance [31] , reduced rates of cognitive decline in late adulthood and a reduced risk of dementia [32] . Drawing from research on alcohol and cardiovascular disease [33] , several authors have concluded that for older adults, alcohol consumption in low to moderate doses may in fact be beneficial for the brain and cognition.…”
Section: Level Of Ability Versus Rate Of Change In Ability Over Timementioning
confidence: 99%
“…The number of APOE e4 alleles carried by each subject was determined by HhaI digestion of PCR products amplified from genomic DNA. 22 …”
mentioning
confidence: 99%